دراسة أهم الخصائص البيولوجية والصفات الظاهرية الكمية للسلالات المنتخبة من عشائر البامية الحورانية - معلا, محمد; بوراس, متيادي; أبو جيش, منار (Latakia University Journal -Biological Sciences Series, 2018)
جرى البحث في مركز بحوث درعا لموسمين زراعيين متتالين 2003 و2004 بهدف دراسة أهم الخصائص البيولوجية والصفات الاقتصادية الكمية للسلالات الناتجة عن تطبيق الانتخاب الفردي للنباتات, على تسع عشائر من البامية جمعت من مناطق محافظة درعا. جرى انتخاب النباتات في الموسم 2003 بالاعتماد على عدد من الصفات التي أظهرت ارتباطاً مع الإنتاجية (عدد الثمار على النبات، عدد الأفرع على النبات), ومع الباكورية (عدد العقد غير الثمرية، عدد السلاميات على الساق، متوسط وزن الثمرة). زرعت بذور النباتات المنتخبة في الموسم 2004 بطريقة نبات/ خط plant / row لتمثل سلالات الجيل الأول من الانتخاب. تباينت السلالات المنتخبة في معظم الصفات حيث تراوحت الباكورية في النضج بين 62 و75 يوم للسلالات (2 و8) على التوالي، وتراوح ارتفاع أو ل قرن بين15 سم للسلالات (2 ، 3 ، 9 ) ، و28 سم للسلالة (7)، كما تباين ارتفاع الساق من 120 سم للسلالة (1) إلى 375 سم للسلالة(8 ) وكذلك إنتاجية النبات الواحد حيث تراوحت القيم بين318 غ للسلالة(7) و541 غ للسلالة ( 2 ) كما تراوح متوسط وزن الثمرة بين 4 غ للسلالة (9) و6.5غ للسلالة(5) وتراوح عدد الثمار على النبات من 74 ثمرة للسلالة (7) إلى 115ثمرة للسلالة(2). درست العلاقة الارتباطية لإنتاجية النبات مع عدد من الصفات للطرز المدروسة فكانت قيم معامل الارتباط مع كل من عدد الأيام حتى النضج، وعدد الأفرع الكلي على النبات ايجابية ضعيفة(r=0.28), بينما كانت مرتفعة مع عدد الثمار على النبات .(r=0.82) كما كان الارتباط كبيراً بين عدد الأيام حتى النضج وكل من عدد العقد غير الثمرية (r=0.75) وعدد السلاميات على الساق الرئيسية (r=0.69) في حين ارتبط عدد الأيام حتى النضج سلباً مع متوسط وزن الثمرة(r= -0.52). قيم درجة التوريث العامة كانت مرتفعة ً, حيث بلغت 0.61 لصفة ارتفاع النبات و0.92 لصفة الباكورية في الإزهار و0.93 لصفة الباكورية في النضج. كما تراوحت قيم الربح الوراثي من 21.1 % لصفة عدد الأيام حتى أو ل زهرة إلى 56.8 % لصفة ارتفاع أو ل ثمرة على النبات. This research was carried out in the Agricultural Research Center of Dara، a during the seasons 2003-2004 in order to study the biological and economic features of some lines, resulting from applying individual plant selection to nine okra populations collected from Dara، a Governorate. The plants were selected in 2003 depending on some traits correlated with yield (number of pods/plant، and number of branches/plant), and correlated with earliness (node number of first flower, number of nodes on main stem, and average weight of pod). Seeds of selected plants were planted as plant / row in the season 2004 to be the first generation of selection. Selected lines differed in days to harvest between 62 and 75 days from sowing for lines (2,8) respectively, height of first pod extended from 15 cm in lines (2, 3, 9) to 28 cm in line (7), plant height extended from 120 cm for line (1) to 375 cm for line (8), for total yield /plant line (2) had the highest yield (541 g), and line (7) had the lowest yield (318g), the average weight of pod ranged between 4g for the line (9) and-5.6 g for line (5). The number of pods / plant ranged from 74 pods for line (7) and 115 pods for line (2). The results showed a slight correlation between yield, and both days to harvest and the number of branches (R=0.28), while it was strong with number of pods/plant (R=0.82). However correlation was strong between days to harvest and both number of none fruiting nodes(R=0.75), and the number of nodes on the main stem (R= 0.69), meanwhile days to harvest correlated negatively with the average weight of the pod (R=-0.52) . Heritability estimates were high, and varied between 0.61 for plant height, 0.92 for early in flowering, and 0.93 for early harvesting. On the other hand, estimates of genetic advance extended from 21.1% for days of flowering and 56.8% for height of the first pod.